GAGASAN KEBIJAKAN HUKUM PIDANA TERHADAP KRIMINALISASI HUBUNGAN SEKSUAL SEJENIS DI INDONESIA - Salsa Annisya Anggraini; Zulfikar Jayakusuma; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Criminal Code Drafting Team made an effort to renew the offense of similar sexual relations , namely regarding obscene perpetrators who are of the same age as other people of the same sex who are known to be not old enough as stipulated in positive law in the 2017 Penal Code Draft Article 495 Paragraph (1) includes namely providing age limit, and an increase in criminal sanctions, which were originally sentenced to five years imprisonment in Article 292 of the Criminal Code to a maximum of 9 years. In addition to giving rise to pros and cons, this is exacerbated by the protracted discussion of the RKUHP, which has not yet been approved, since 1963 until the idea of criminal law policy arises in the criminalization of similar relations in article 292 of the Criminal Code for conducted a judicial review by the Court Constitution but precisely rejected the lawsuit on the grounds that as tested by the applicant is not the authority of Court Constitution as negative legislato r . The impact of these types of sexual acts can damage the moral values and religious rallies that exist in Indonesian society based on almighty divinity, so that these actions will gradually become legalized because there are no legal rules in positive Indonesian law and be a threat to national identity, meanwhile there are a number of countries which can regulate criminal sanctions against similar sexual relations , such as Malaysia and Nigeria. The purpose of writing this thesis, namely; First, to find out the urgency of criminal law policies in the criminalization of similar sexual relations in Indonesia . Second, to find out the criminal law policy towards similar sexual relations in Indonesia .This type of research used in this legal research is the normative juridical method , this research is descriptive, which is a study that aims to make a clear and detailed description of the problem . Data sources used secondary data and tertiary legal materials . Techniques of collecting data in this study with the methods of literature study after the data is collected and analyzed to be drawn kesimpulan.Dari results of research and discussion can be concluded that the U rgensi criminal law policy in criminalizing same-sex relations in Indonesia , because it has a lot of unrest in the community reap Indonesia, uphold eastern customs .. Keywords: Legal Policy - Criminalization - Similar Sexual Relations